Contemporary Spoliation: Productive Reuse in Francesco Venezia's Projects - Condello, Annette (FedOA - Federico II University Press, 2020)
From the mid-1970s onward, Neapolitan architect Francesco Venezia generated intriguing reuse projects, in and out of sync with other postmodernists of his era, and his writings on ‘architectural spoils’ are most influential today when regenerating cities. Venezia’s work, such as Lauro Square (1976), critically interrogates Naples’ pre-Christian palimpsest as spaces of spolia. He embraces the constructed landscape and luxurious spolia of the antiquity of Egypt, Paestum and Pompeii. Additionally, he embraces the complexity of Naples’ archaeological remnants and modern architectural history with the unveiling of hidden poetic qualities of their fragments within Le Corbusier’s writing and sketches. This paper will expand on previous research on the writings and projects by Venezia, by tracing the modern and contemporary fragmentation within his designs. The paper will briefly look at Venezia’s reuse projects at Caserta (2014) and Pompeii (2015), which present important arguments for establishing and interpreting the reuse of spolia between antiquity and the modern. Projecting a new understanding on architectural spoliation, by positioning the discussion outside mainstream postmodern discussions, it argues that Venezia’s meaningful projects embrace the idea of palimpsest and that contemporary regenerating of city-landscapes contribute to producing environments that eliminate wasted spaces.